Pemikiran Abdurrahman Wahid Tentang Islam dan Pluralitas - Zainal Abidin (Humaniora, 2012)
This article clarifies a research that concerned with Wahid’s thoughts and actions that saw Islam from its basic value, not merely as a symbol. Therefore, Wahid presented Islam from democratic and cultural sides. To present the phylosophical analysis of Wahid’s thoughts, the research applies hermeneutics approach and library research, especially reading Wahid’s books as the primary sources, and others’ books related to Wahid’s thoughts as the secondary sources. It can be concluded that Islam presented by Wahid is the Islam that relates to softness, adoring loves, defending the weakness and minority, sustaining to lead the justice, having faith and honesty, tolerance, inclusive, and showing plualities.